JOB SATISFACTION AMONG THE PRIMARY TEACHERS: A CASE STUDY OF SENAPATI DISTRICT, MANIPUR - KOMOW, B. (THE PRIMARY TEACHER, 2013)
Teachers are regarded as one of the most important group of professionals for nation building. As the teachers are directly involved in the academic progress of the children and educational system, their job satisfaction is prerequisite to imparting quality education. Job satisfaction of the teachers is also directly linked with their competence and effectiveness. If educational policies are formed taking researches into consideration, there can be more realistic resulting improved in proficiency of teachers. This can also contribute towards the successful outcome of education programmes being undertaken in the country. The study is an attempt to assess the job satisfaction of primary teachers in Senapati District of Manipur